Israel's poetry of resistance : Africana perspectives on early Hebrew verse - Page, Hugh R. (Minneapolis : Fortress Press, 2013)
"Noting that Israel's earliest responses to earth-shaking changes were cast in the powerfully expressive language of poetry, Hugh R. Page Jr. argues that the careful collection and preservation of these traditions was an act of resistance, a communal no to the forces of despair and a yes to the creative power of the Spirit. Further, Page argues, the power of these poems to craft and shape a future for a people who had suffered acute displacement and marginalization offers a rich spiritual repertoire for Africana peoples today, and for all who find themselves perennially outside the social or political mainstream. Here Page offers fresh translations and brief commentary on the Bible's fifteen earliest poems, and explores the power and relevance of these poems, and the ancient mythic themes behind them, for contemporary life at the margins"--Publisher's description.
Part I: The Bible and Africana reality. Wilson Park, Homewood, and early Hebrew verse : an Africanan perspective on the Albright tradition -- Diasporas and adaptive stategies in early Hebrew verse and the Africana world -- Part II: Early Hebrew poems : a compendium of Africana readings. Zora Neale and the lawgiver in conversation : Exodus 15 and Moses, man of the mountain -- The Song of Deborah : Harriet, Ben, Jael, and "Jah work" -- The destructive power of the almighty : Grenada, Ivan, Soufrière Hills, and Psalm 29 -- Playing "the dozens" and community formation : rethinking Genesis 49 and Deuteronomy 32-33 -- "Somebody done hoodooed the hoodoo man" : Junior Wells, Balaam, and the persistence of conjure -- "Something got a hold of me" : 1 Samuel 2 and aged Black bodies -- Harmolodic blues and an esoteric mash-up : reengaging 2 Samuel 1; 22 (Psalm 18); 23; and three ancient Psalms (68, 72, and 78) -- Part III: Preaching, teaching, and living early Hebrew poems. Early Hebrew poetry : engaging it in Africana congregational settings -- Recovering poetry as way of life in the Africana world, the church, and beyond -- Conclusion: Early Hebrew poetry and spiritualites of resistance in the Black Atlantic -- Blues note : a poetic afterword.
Includes bibliographical references (pages 133-139).
Keywords: Bible. -- Black interpretations; Hebrew poetry, Biblical -- History and criticism; Hebrew poetry, Biblical -- Translations into English